An archaeometric study of the Phoenician ceramics found at the São Jorge Castle's hill in Lisbon - Ferreira, L. F. Vieira (2020)
A detailed archaeometric study of Phoenician ceramics found in an excavation inside the medieval walls of São Jorge's Castle in Lisbon is described here. Thirty ceramic sherds were studied, grouped into six categories, namely amphorae, containers for domestic use, red slip wares, grey wares, cooking wares and also some indigenous tradition handmade wares. Micro-Raman, X-Ray Fluorescence Emission, X-Ray Diffraction and ground state diffuse reflectance absorption measurements were correlated and used as our main analytical techniques to perform this study. At least three totally different local clay sources were used to produce the here studied pottery, one of alluvial origin using clays collected along the river banks, and another one using clays probably extracted in the oriental part of the Castle's hill. Cooking-ware was made with the use of raw materials with sandy detrital origin. Evidence was also found showing that part of the amphorae, common containers, and grey wares were made with the same raw materials as used in the Phoenician kilns of Almaraz, located in the left margin of the Tagus River, roughly facing Lisbon's Castle hill. The temperatures of the kilns used to fire the amphorae and common containers was in most cases higher than the one used for firing red slip and grey tableware. A detailed laboratorial study of the alluvial clays fired at different temperatures and collected in the Tagus River banks, allowed us, in most cases, to establish the origin of the sources used to produce the Phoenician pottery found in Lisbon.